The Conceptual Autonomy of the Babylonian World. Translation by T. Jacobsen, B. Foster, H. von Siebenthal. Introduction by T. Jacobsen - Landsberger, Benno
translation of Die Eigenbegrifflichkeit der babylonischen Welt, Islamica 2 (1926) 355-372.